Sedimentology of the Paleogene Volcaniclastic Gravity Flow Deposit of the Ulukışla Formation, South Central Türkiye (Rudarsko-geološko-naftni zbornik, 2024)
The sedimentological study of volcaniclastic successions is essential for gaining insight into the intricate geological history of the Ulukışla Basin in south Central Anatolia. This study, based on a comprehensive facies analysis of two representative stratigraphic sections, attempts to reconstruct the depositional conditions associated with volcaniclastic sedimentation within the Ulukışla Formation. Facies assemblages dominated by debris-flow deposits and turbidites provide clear evidence for deposition under deep-water conditions related to the proximal environment. Sedimentary characteristics of these deposits made up of volcanogenic conglomerates with basaltic to andesitic clasts of variable size, sandstones, and subordinate mudstone are suggestive of derivation from the nearby Ulukışla volcanic rocks. Almost all the lithofacies display a high tuff content indicative of possible sediment contributions from sub-aerial volcanic sources. The main controlling factors responsible for deposition include submarine gravity flow processes thought to have been triggered by slope instability or the collapse of a volcanic edifice. Thus, the resulting volcaniclastic accumulations are interpreted to be linked to volcanic apron deposits. In the realm of prospective research, the acquisition of geochemical and geochronological data stands as a promising avenue, offering crucial insight into the temporal aspects and tectonic setting of deposition of the Ulukışla volcaniclastic sequence.